Histories-argeologiese ondersoek na die militêre fortifikasies van Pretoria (1880-1902) - Ferreira, O.J.O. (Ockert Jacobus Olivier), 1940- (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 1992.